2014
DOI: 10.1111/vcp.12154
|View full text |Cite
|
Sign up to set email alerts
|

Negative interference of icteric serum on a bichromatic biuret total protein assay

Abstract: Background Bilirubin is stated to be a negative interferent in some biuret assays and thus could contribute to pseudohypoproteinemia in icteric samples. Objective The purpose of the study was to evaluate the magnitude of and reason for a falsely low total protein concentration in icteric serum when the protein concentration is measured with a bichromatic spectrophotometric biuret assay. Methods Commercially available bilirubin was dissolved in 0.1 M NaOH and mixed with sera from 2 dogs to achieve various bilir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Previous studies have documented decreased TP biuret with unconjugated bilirubin values as low as 14 mg/dL, or minimal differences in TP biuret with bilirubin up to 30 mg/dL . A significant negative and proportional interference of TP biuret with hyperbilirubinemia near 10 mg/dL has been previously observed . Therefore, it is reasonable to assume that the high bilirubin concentration of 81 mg/dL in this dog contributed to the low TP biuret , although intravenous fluid administration may have also contributed to the decreased TP biuret .…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies have documented decreased TP biuret with unconjugated bilirubin values as low as 14 mg/dL, or minimal differences in TP biuret with bilirubin up to 30 mg/dL . A significant negative and proportional interference of TP biuret with hyperbilirubinemia near 10 mg/dL has been previously observed . Therefore, it is reasonable to assume that the high bilirubin concentration of 81 mg/dL in this dog contributed to the low TP biuret , although intravenous fluid administration may have also contributed to the decreased TP biuret .…”
Section: Discussionsupporting
confidence: 60%
“…Despite this disadvantage, the biuret assay is still frequently used because of its simple analytical procedure and the easy preparation of reagents. Further, compared with other copper-based assays this method is less susceptible to chemical interference (Gupta and Stockham 2014). Moreover, many of the assay kits developed for automated use in wet biochemical analysers, as well as dry chemistry analysers, are based on this principle.…”
Section: Total Proteinmentioning
confidence: 99%
“…These methods can have variable performance based on the number and type of protein species present in the sample, and minor interference can be caused by peptides and free amino acids . Additionally, icterus can cause interference with the biuret method . A survey revealed that only 2.4% of 842 participating human laboratories used refractometry‐based total protein quantification for SPE .…”
Section: Methodsmentioning
confidence: 99%